2018
DOI: 10.1021/acs.jpcc.8b07606
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Poly-l-lysine Molecules in Electrolyte Solutions: Modeling and Experimental Measurements

Abstract: Physicochemical properties of poly-L-lysine (PLL) hydrobromide were determined by Molecular Dynamics (MD) modeling and a variety of experimental techniques. Primarily, the density, the chain diameter, the monomer length and PLL molecule conformations were theoretically calculated. These results were applied for the interpretation of experimental data acquired for 2 PLL sample of the average molar mass equal to 122 kg/mol. They comprised the diffusion coefficient, the hydrodynamic diameter and the electrophoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(90 citation statements)
references
References 84 publications
6
83
1
Order By: Relevance
“…The increase in the adsorbed mass with the initial bulk concentration of poly- l -lysine, having an elongated shape, 74 was also observed in studies by Kosior et al ( 75 ) Similar to the results obtained from the OWLS, no desorption of λ-car molecules from both bilayer types was observed.…”
Section: Resultssupporting
confidence: 84%
“…The increase in the adsorbed mass with the initial bulk concentration of poly- l -lysine, having an elongated shape, 74 was also observed in studies by Kosior et al ( 75 ) Similar to the results obtained from the OWLS, no desorption of λ-car molecules from both bilayer types was observed.…”
Section: Resultssupporting
confidence: 84%
“…Recently, viscosity measurements have showed that the PLL has an extremely extended conformation at pH 5.6. 16 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The finite-size effects rising from the peptide chain length should be negligible for the highly charged polypeptides at low ionic strength, because the electrostatic repulsions make the peptide end-to-end distance then linearly dependent on the molar mass. 16 On the other hand, for the low ionization degrees, it is very likely that longer peptides would fold onto themselves more than these short segments. However, examining this would need a significantly longer equilibration and larger box size, which makes such simulations computationally very demanding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-L-lysine hydrobromide (PLL), a synthetic polypeptide having a molar mass of 75-189 kg mol −1 (determined by MALS), was purchased from Sigma Aldrich Merck KGaA, Darmstadt, Germany. The average molar mass of the PLL sample of 120 kg mol −1 was more precisely determined by dynamic viscosity measurements [43].…”
Section: Methodsmentioning
confidence: 99%